2001
DOI: 10.1103/physrevlett.86.4447
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid and Dissipative Dynamics of a Bose-Einstein Condensate in a Periodic Optical Potential

Abstract: We create Bose-Einstein condensates of 87 Rb in a static magnetic trap with a superimposed blue-detuned 1D optical lattice. By displacing the magnetic trap center we are able to control the condensate evolution. We observe a change in the frequency of the center-of-mass oscillation in the harmonic trapping potential, in analogy with an increase in effective mass. For fluid velocities greater than a local speed of sound, we observe the onset of dissipative processes up to full removal of the superfluid componen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
376
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(397 citation statements)
references
References 28 publications
19
376
1
1
Order By: Relevance
“…We also observe the appearance of an intermediate regime where no oscillations are visible while the relative phase coherence is not completely lost. In a previous experiment we have investigated the regime of small periodic potential height, showing that in this regime and for large atom numbers, the mechanism for superfluidity breakdown was in agreement with predictions based on the onset of the Landau instability [12]. In the present experiment we explore the dynamics of the system in the case of a large periodic potential height, where a modulational instability is expected to play a fundamental role [8,9].…”
supporting
confidence: 81%
“…We also observe the appearance of an intermediate regime where no oscillations are visible while the relative phase coherence is not completely lost. In a previous experiment we have investigated the regime of small periodic potential height, showing that in this regime and for large atom numbers, the mechanism for superfluidity breakdown was in agreement with predictions based on the onset of the Landau instability [12]. In the present experiment we explore the dynamics of the system in the case of a large periodic potential height, where a modulational instability is expected to play a fundamental role [8,9].…”
supporting
confidence: 81%
“…[2,3,4,5,6,7,8]). Coupling between the BEC droplets localized in weakly interacting minima of a standing light wave creates a reconfigurable matter-wave structure that can be easily manipulated by varying the strength of the periodic potential and its well spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Let us now discuss dipole oscillation. In the experiment for 3-D BEC [36], the trap in the presence of the optical lattice was suddenly shifted. It was observed that the subsequent oscillations of the BEC are undamped if the initial displacement is small, but become dissipative if the initial displacement exceeds a critical value.…”
Section: Accordion Latticementioning
confidence: 99%
“…Due to strong quantum fluctuations, mean-field theories fail for the description of the system. Consider an experiment like the ones in [36,37] to study dipole oscillation for an accordion lattice. The amplitude of the small dipole oscillation increases with Λ without leading instability since the lattice is expanding (5).…”
Section: Accordion Latticementioning
confidence: 99%